La politicidad inmanente del arte y el derecho (Tema Central) - Zambrano Álvarez, Diego (2019)
In this article, the author pretends to show, the political function of art and law, like creation of an artificial world designed by elites for their control and benefit. However, it is argued that the Latin American law and art have entered in a new version, born than its own identity, juridical and esthetics forms, with which pretends develop a new version of constitutionalism, since its culture baroque, popular and mixed between the European and native matrix. With all this, the Latin-American countries pretends overcome the challenges of postmodernity predatory, consumerist and globalized.